Impact of storage on the physiological quality of soybean seeds after treatment with fungicides and insecticides - Del Bem Junior, Luciano [UNESP] (2020)
Chemical seed treatment is a practice that assists in control of pests and pathogens and allows crops to achieve their maximum yield potential. However, the storage period of seeds treated with insecticides and fungicides can affect seed physiological potential. The aim of this study was to evaluate the physiological quality of soybean seeds treated with different fungicides and insecticides after four different storage periods. The experimental design was completely randomized and the treatments were distributed in a 10 × 4 factorial arrangement in which the soybean seeds of the cultivar BMX Potência RR were treated with the following phytosanitary products: fipronil + pyraclostrobin + thiophanate-methyl, thiophanate-methyl, carbendazim, carboxin + thiram, imidacloprid + thiodicarb, chlorantraniliprole, thiamethoxam, cyantraniliprole, fipronil, and a control (seeds without chemical treatment), in four replications. The seeds were evaluated at 0, 30, 60, and 90 days after the chemical treatment. The following tests were performed: germination, first count of germination, accelerated aging, seedling emergence in sand, seedling emergence speed, and seedling dry matter. The treatment with the carboxin + thiram fungicide mixture provided for adequate physiological quality of the seeds throughout storage. The insecticide thiamethoxam has a negative effect on the physiological quality of soybean seeds that are stored after treatment with it.